CYTOKINE IMMUNITYINCKD PATIENTS TREATED WITH HD, HDF, PD - Dryanska, V.E.; Dudar, I.O.; Shifris, I.; Gonchar, Yu.I.; Loboda, O.M.; Galsenluk, F.Z.; Krot, V.F. (Ukrainian Journal of Nephrology and Dialysis, 2016)
Introduction. Cytokines play the corresponding role in the inflammatory processes and the development of endothelial dysfunction and therefore take an important place in the problem of systemic chronic inflammation (SCI) in patients with chronic kidney disease (CKD), stage V, who are treated with methods of the renal replacement therapy (RRT). Aim of the work was to determine the features ofpro- and anti-inflammatory cytokines, VEGF in patients with CKD stage V D, depending on the method of RRT (HD, HDF, PD). Materials and methods. There were examined 56 patients with CKD, st. V treated with methods of RRT: gr.1 received hemodialysis (HD) (15 p), gr. 2 - hemodiafiltration (HDF) (28 p) and gr. 3 – peritoneal dialysis (PD) (13p). The cytokines levels (IL-6, -8, -10, -18, TNF-a, VEGF) were determined in blood serum by means of ELIZA. Results. The CKD, st. V patients treated with RRT showed really increased levels of pro-inflammatory blood cytokines (TNF-a, IL-8, IL-18) (p < 0.001) and VEGF as important factor of endothelial dysfunction, in dependence on RRT the groups 1-3 did not differ (p > 0.05). In comparison with healthy donors, in patients of gr. 3 the level of antiinflammatory IL-10 was the highest (p < 0.001) in comparison with gr.1 (p = 0.080) andgr.2 (p = 0,043) (corresponding HD and HDF), and the ratio IL-18/IL-10 was really more low in comparison with both other groups (p = 0.035). Conclusion. The high level of serum cytokines confirms the SCI availability in patients with CKD,st.V; the patients treated with PD showed the lower degree of inflammatory reactions by the data of balance between pro/anti-inflammatory immunity mediators.